2022
DOI: 10.3389/fonc.2022.919522
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Circulating Metabolites and Lipoproteins After Breast Cancer Treatment

Abstract: The multimodal treatment of breast cancer may induce long term effects on the metabolic profile and increase the risk of future cardiovascular disease. In this study, we characterized longitudinal changes in serum lipoprotein subfractions and metabolites after breast cancer treatment, aiming to determine the long-term effect of different treatment modalities. Further, we investigated the prognostic value of treatment-induced changes in breast cancer-specific and overall 10-year survival. In this study, serum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…In addition, t-C/HDL-C correlations with BFP (0.4) and LMP (-0.4) were noted. As the lipid profile has been pointed out as a risk factor for atherogenic progression and the development of cardiovascular diseases in BCS [10,18], such findings corroborate the above reasoning and support this integrated network between anthropometric and biochemical aspects.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, t-C/HDL-C correlations with BFP (0.4) and LMP (-0.4) were noted. As the lipid profile has been pointed out as a risk factor for atherogenic progression and the development of cardiovascular diseases in BCS [10,18], such findings corroborate the above reasoning and support this integrated network between anthropometric and biochemical aspects.…”
Section: Resultssupporting
confidence: 77%
“…In the history of BCS, either by the disease itself or by the treatments performed, changes in anthropometry [4,5], fatigue level [6], muscular strength [7], hematologic variables [8], lipid profile [9,10], and cell membrane properties [11,12], among others, are common findings. These changes are not limited to an isolated category as they reach various health indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Its performance is based on developing risk strategies (either primary or secondary) for prevention and intervention aimed at reducing CV risk, preventing cardiotoxicity, and managing adverse effects ( 20 , 21 ). Epidemiological trends demonstrate the apparent association between cancer, its therapies, and CV events, whether they are outcomes (as proven in other studies) or profile changes [as demonstrated by Giskeødegård et al ( 1 )]. This work is yet another demonstration of the critical role and the need for this specialty to be increasingly integrated into the care of cancer patients, acting through proposals and interdisciplinary teams to make the care of these patients as qualified as possible ( Figure 1 ).…”
Section: The Role Of Cardio-oncologymentioning
confidence: 85%
“…This commentary builds upon the recent paper by Giskeødegård et al (1) to complement and advance the debate about the cardiovascular (CV) effects of cancer treatment. The aim is to discuss the practical implications of the findings and how this can change cancer care.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, measurements of lipoprotein subfractions, the main carriers of triglycerides and cholesterol in the blood stream, provide extensive information on metabolic activity and may be reflective of an individual’s health status. Data from clinical treatment trials in other solid tumors signify that the metabolite and lipoprotein composition in blood can predict the response to therapy, prognosis, and long-term risk for cardiovascular disease [ 20 , 21 ]. How the treatment regimens recommended to patients with HGSOC influence their metabolic balance is still unclear [ 22 ].…”
Section: Introductionmentioning
confidence: 99%